The Effect of Service Quality, Promotion and Word of Mouth on The Purchase Interest of Aquarium Consumers at The Sakti Aquarium Pamulang Store - Ramadhan, Firzatullah; Tajuddien, Rahadyan (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of service quality, promotion, and word of mouth on consumer purchase intention at Sakti Aquarium Pamulang. The growing public interest in aquascaping and ornamental fish presents significant business opportunities; however, declining sales performance indicates potential marketing weaknesses. Using a quantitative approach with 207 respondents selected via the Slovin formula, data were analyzed using SPSS through validity, reliability, normality, and regression tests. The validity and reliability results confirmed that all research instruments were valid and reliable. The coefficient of determination (R² = 0.037) indicated that service quality, promotion, and word of mouth collectively explained 3.7% of purchase intention, while 96.3% was influenced by other factors. The t-test results revealed that service quality (Sig = 0.44) and word of mouth (Sig = 0.27) had no significant effect on purchase intention, whereas promotion (Sig = 0.07) showed a partial influence. These findings highlight that promotional activities play a more substantial role in shaping consumer interest than service quality or interpersonal recommendations. The study provides practical implications for improving marketing strategies in the aquarium retail sector and contributes to the broader understanding of consumer behavior in niche lifestyle industries.